Adherence to subcutaneous anti‐TNFα agents in patients with rheumatoid arthritis is largely influenced by pain and skin sensations at the injection site. (2nd March 2020) - Salaffi, Fausto; Di Carlo, Marco; Farah, Sonia; Carotti, Marina
Abstract: Aim: The aims of this prospective study were to determine the dimension of adherence in rheumatoid arthritis (RA) patients receiving subcutaneously administered anti‐tumor necrosis factor‐α (anti‐TNFα) agents and to evaluate the influence of injection site pain and skin perceptions following subcutaneous administration of anti‐TNFα drugs on patients' adherence. Method: An inception cohort of patients starting subcutaneously administered anti‐TNFα treatment was enrolled. Injection site pain perception was assessed through the Self‐Injection Assessment Pain Questionnaire (SIAPQ), and adherence to treatment was ascertained by the Compliance Questionnaire for Rheumatology (CQR5). Associations between beliefs and non‐adherence, and the influence of demographic (age, disease duration, educational level), clinical (body mass index, patient global assessment, physician global assessment, Numerical Rating Scale of pain, Health Assessment Questionnaire–Disability Index, Simplified Disease Activity Index, and comorbidities measured by the modified Rheumatic Disease Comorbidty Index), and radiographic (Simple Erosion Narrowing Score) variables were assessed using logistic regression models. Results: Adherence data over a 12‐month interval were available for 193 patients. Of these, 21.7% reported non‐adherence to anti‐TNFα therapy. No difference ( P  = .383) was found for anti‐TNFα drugs (adalimumab, etanercept, certolizumab pegol and golimumab). In the logistic model, age ( P  = .0029), higher disease activity ( P  = .020), low numbers of comorbidity conditions ( P  = .0004), injection site pain and skin perception ( P  = .0008), were significantly associated with increased likelihood of medication adherence. Conclusion: Adherence is influenced by both demographic characteristics (age) and clinical factors (disease activity, comorbidity burden and injection site pain and skin perception) in RA patients.